1838 Va. Acts 76, ch. 101, § 1 - (:unkn) unknown (My University, 1838)
It is against the law to habitually or generally keep or carry about his person any pistol, dirk, bowie knife, or any other weapon of the like kind . . . hidden or concealed from common observation.
Keywords: CARRY - CONCEALED